Integration of topology optimisation tools and knowledge management into the virtual Product Development Process of automotive components. (6th September 2011) - Muzzupappa, Maurizio; Barbieri, Loris; Bruno, Fabio
This paper presents a methodology in which CAD, a multi-body simulator and a Topological Optimisation (TO) tool are synergically employed to support the design of a suspension component. In particular, the methodology defines some guidelines and introduces two knowledge-based interfaces able to facilitate the integration of TO of the component within a standard design process. To illustrate this capability, the process is applied to the conceptual design of the Upright for a Formula SAE prototype. The results show that the integrated design approach can efficiently support the selection of the optimum conceptual design of a mechanical component with complex dynamic behaviour, in particular when very little previous experience on the system is available.